2020
DOI: 10.1111/jar.12850
|View full text |Cite
|
Sign up to set email alerts
|

Participation in employment and day care for adults with intellectual disabilities: Equal access for all?

Abstract: Equal rights to employment for people with intellectual disabilities are also included in the UN's Convention on the Rights of Persons with Disabilities (CRPD) (United Nations, 2006, Article 27). Nonetheless, a decline in employment and day care participation has been recordedamong people with intellectual disabilities in Norway Søderstrøm & Tøssebro, 2011); in 2015, more than half were registered as neither employed nor in municipal day care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…More than 90% of these employed participants worked in sheltered employment (NOU, 2016, p. 17). More recently in a large study ( n = 14,517), Engeland et al (2021) reported 26.1% registered in sheltered employment or facilitated jobs with support among people with intellectual disabilities in Norway. Only people registered in public daycare, sheltered employment or facilitated jobs with support were included in the Norwegian report and the study by Engeland et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More than 90% of these employed participants worked in sheltered employment (NOU, 2016, p. 17). More recently in a large study ( n = 14,517), Engeland et al (2021) reported 26.1% registered in sheltered employment or facilitated jobs with support among people with intellectual disabilities in Norway. Only people registered in public daycare, sheltered employment or facilitated jobs with support were included in the Norwegian report and the study by Engeland et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…A more thorough evaluation of the individuals' wishes and prerequisites, making Affairs, 2002). Still, no evaluation of the needs and resources of people with intellectual disabilities is required by law before a disability pension is granted (Engeland et al, 2021). Most people with intellectual disabilities are granted a disability pension at the age of 18 and are thus perceived by the Norwegian welfare-system to have low capacity for work (Proba, 2016).…”
Section: Variables Associated With Employment In the Multivariate Log...mentioning
confidence: 99%
See 2 more Smart Citations
“…Johora, Fleer & Hammer 2021 ; Kunz, Luder & Kassis 2021 ; Reese 2021 ), just in excess of one in 10 was about inclusion in employment and the workplace (e.g. Clube & Tennant 2021 ; Engeland et al 2021 ), and the remainder (one-quarter) covered the legal aspects of inclusion (e.g. Buckley & Quinlivan 2021 ), or dealt with inclusion in religion (e.g.…”
Section: Introductionmentioning
confidence: 99%